Relationship between expression of the family of M proteins and lipoteichoic acid to hydrophobicity and biofilm formation in Streptococcus pyogenes. - Harry S Courtney (Public Library of Science (PLoS), 2009)
Background Hydrophobicity is an important attribute of bacteria that contributes to adhesion and biofilm formation. Hydrophobicity of Streptococcus pyogenes is primarily due to lipoteichoic acid (LTA) on the streptococcal surface but the mechanism(s) whereby LTA is retained on the surface is poorly understood. In this study, we sought to determine whether members of the M protein family consisting of Emm (M protein), Mrp (M-related protein), Enn (an M-like protein), and the streptococcal protective antigen (Spa) are involved in anchoring LTA in a manner that contributes to hydrophobicity of the streptococci and its ability to form biofilms. Methodology/principal findings Isogenic mutants defective in expression of emm, mrp, enn, and/or spa genes of eight different serotypes and their parental strains were tested for differences in LTA bound to surface proteins, LTA released into the culture media, and membrane-bound LTA. The effect of these mutations on the ability of streptococci to form a hydrophobic surface and to generate biofilms was also investigated. A recombinant strain overexpressing Emm1 was also engineered and similarly tested. The serotypes tested ranged from those that express only a single M protein gene to those that express two or three members of the M protein family. Overexpression of Emm1 led to enhanced hydrophobicity and biofilm formation. Inactivation of emm in those serotypes expressing only a single emm gene reduced biofilm formation, and protein-bound LTA on the surface, but did not alter the levels of membrane-bound LTA. The results were more varied in those serotypes that express two to three members of the M protein family. Conclusions/significance Our findings suggest that the formation of complexes with members of the M protein family is a common mechanism for anchoring LTA on the surface in a manner that contributes to hydrophobicity and to biofilm formation in S. pyogenes, but these activities in some serotypes are dependent on a trypsin-sensitive protein(s) that remains to be identified. The need for interactions between LTA and M proteins may impose functional constraints that limit variations in the sequence of the M proteins, major virulence factors of S. pyogenes.